THE INFLUENCE OF HOTEL MANAGEMENT POLICIES AND MARKETING STRATEGIES ON CUSTOMER TRUST TO STAY AT THE SUTOMO GUEST HOUSE MEDAN HOTEL IN THE COMING TIME (POST COVID-19 PANDEMIC) - Reja Ferdynanta; Elisabet Tambunan (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
2020 is a very difficult year for some countries due to the Covid-19 virus outbreak that has hit countries around the world. Covid-19 is a virus originating from China, precisely in the city of Wuhan. This virus has a very fast transmission, as a result of which many citizens of the country are quickly infected by this virus. The government in a number of countries, especially Indonesia, applies social restrictions and calls for all activities from home. As a result, the tourism sector has experienced a significant decline. This study entitled